2021
DOI: 10.1097/cce.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Risk Prediction for Hospital-Acquired Pressure Injury in Adult Critical Care Patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Previous research has found that patients with PIs are more likely to suffer severe complications. [12][13][14][15] In the present study, patients in the PI group had a higher incidence of various postoperative adverse events and longer hospital and ICU lengths of stay, in comparison with the non-PI group. According to the literature, risk factors related to postoperative PI include age, high BMI, heart failure, diabetes, low preoperative Braden Scale score, and operation duration.…”
Section: Discussionsupporting
confidence: 43%
“…Previous research has found that patients with PIs are more likely to suffer severe complications. [12][13][14][15] In the present study, patients in the PI group had a higher incidence of various postoperative adverse events and longer hospital and ICU lengths of stay, in comparison with the non-PI group. According to the literature, risk factors related to postoperative PI include age, high BMI, heart failure, diabetes, low preoperative Braden Scale score, and operation duration.…”
Section: Discussionsupporting
confidence: 43%
“…Several intrinsic and extrinsic risk factors for IAPIs already have been identified in patients undergoing surgery 25 . Undoubtedly, previous studies have shown that the use of vasoconstrictors such as norepinephrine and vasopressin plays a crucial role in the occurrence of PI, as these drugs promote peripheral vascular contraction and may lead to peripheral tissue ischemia 26,27 . Norepinephrine and vasopressin were significantly associated with development of pressure ulcers; vasopressin was the only significant predictor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 97%
“…25 Undoubtedly, previous studies have shown that the use of vasoconstrictors such as norepinephrine and vasopressin plays a crucial role in the occurrence of PI, as these drugs promote peripheral vascular contraction and may lead to peripheral tissue ischemia. 26,27 Norepinephrine and vasopressin were significantly associated with development of pressure ulcers; vasopressin was the only significant predictor in multivariate analysis. In addition, MAP <60 mmHg in patients receiving vasopressors was predictive of development of pressure ulcers.…”
Section: Blood Pressure Iapismentioning
confidence: 90%
“…Design Sample Size Method Balancing [22] Cohort Retrospective 269 Not Reported [23] Cohort Prospective 648 Not Reported [15] Systematic Reviews 168-188,512 Not Applicable [17] Systematic Reviews 237,397 Not Applicable [24] Cohort Retrospective 486 Not Reported [25] Cohort Prospective 12,654 Random Oversampling [26] Cohort Retrospective 50,851 Synthetic Minority Oversampling and Random Oversampling [14] Cohort Retrospective 6376 Random Oversampling [4] Experimental Design 11,838 Under Sampling and Random Oversampling [16] Systematic Reviews and Meta 125,213 Not Applicable [27] Cohort Retrospective 100,355 Not Reported [28] Cohort Retrospective 4652 Random Oversampling [29] Cohort Retrospective 618 Random Oversampling [30] Cohort Retrospective 75,353 Random Oversampling [31] Case-Control 2341 Under Sampling [32] Cohort Prospective 13,254 Not Reported [33] Cohort Prospective 194 Not Reported [34] Cohort Retrospective 18,019 Not Reported [35] Cohort Prospective 149 Not Reported [36] Cohort Retrospective 15,310 Random Oversampling [37] Cohort Retrospective 9644 Not Reported [38] Cohort Retrospective 5101 Synthetic Minority Oversampling [39] Cohort Retrospective Different studies discussed the use of machine learning in constructing a prediction model for pressure injury; 27 studies were reviewed in the literature in terms of using machine learning to predict pressure injury [4,9,11,13,14,17,[20][21][22][23]26,27,[29]…”
Section: Referencementioning
confidence: 99%
“…[33] Oral mucosal, endotracheal tube, vasopressor, albumin, hematocrit, and steroids. [34] Age, body mass index, lactate serum, Braden score, vasopressor use, and antifungal medications.…”
Section: Referencesmentioning
confidence: 99%